Flux et hauts-lieux du tourisme national brésilien - Hervé Théry (IdeAs)
Brazil is not a major international tourist destination, with only 6.5 million tourists, but domestic tourism is very active (nearly 60 million tourists and 190 million trips) thanks to a national market of more than 200 million people. This has led to the construction of a powerful and well-structured tourism sector, which can be analyzed in a precise manner through official publications available online. They contain abundant data from which we can draw maps that help to locate its strengths and the flows it induces. Analysis of three of the high places of tourism in Brazil, the cataracts of Iguaçu, Paraty and Nossa Senhora Aparecida, allows showing the diversity of the types of tourism and the differentiated effects of the facilities and flows that they induce.